Animal Models of Zika Virus Infection, Pathogenesis, and Immunity - Morrison, Thomas E.; Diamond, Michael S. (Journal of virology, 2017)
Zika virus (ZIKV) is an emerging mosquito-transmitted flavivirus that now causes epidemics affecting millions of people on multiple continents. The virus has received global attention because of some of its unusual epidemiological and clinical features, including persistent infection in the male reproductive tract and sexual transmission, an ability to cross the placenta during pregnancy and infect the developing fetus to cause congenital malformations, and its association with Guillain-Barré syndrome in adults. This past year has witnessed an intensive effort by the global scientific community to understand the biology of ZIKV and to develop pathogenesis models for the rapid testing of possible countermeasures. Here, we review the recent advances in and utility and limitations of newly developed mouse and nonhuman primate models of ZIKV infection and pathogenesis.